Transformation of Malay Manuscript Illumination as Embroidery Motif on Baju Kuruang Basiba - Riza, Yulfira; Ihsania, Nadia; Fitria Utami, Shinta (Journal of Visual Art and Design, 2024)
This study proposes creative industry products with decorative motifs inspired by antique illuminated manuscripts collected by the Leiden University Library. Three illuminated Malay manuscripts were taken, namely: the manuscript with the number Or. 1703 entitled Sejarah Melayu; Or. 1768 entitled Collective Volume with Texts in Malay; and Or. 1967 entitled Hikayat Iskandar Zulkarnain. A descriptive qualitative method was used in this research. Field observation was conducted by interviewing an expert in decorative motifs to achieve the harmony of motifs and aesthetics in baju kuruang basiba. The motif was created using the CorelDrawX7 software. This study created embroidery motifs that can be classified as naturalistic ornaments. The design of decorative motifs for baju kuruang basiba can be embroidered with the suji and kapalo samek techniques. Meanwhile, the material used is a material that does not show because the sewing of baju kuruang basiba does not use furring. The decorative patterns that can be used are rasp patterns and fringe patterns. Baju kuruang basiba is a typical Minangkabau shirt that must be preserved as a cultural heritage object. The addition of this embroidery motif can add to the aesthetic appearance of the shirt to make it more attractive and luxurious.